CHEMICAL MODIFICATION OF BACTERIAL CELLULOSE FOR USE IN REGENERATIVE MEDICINE - Rodriguez-Chanfrau, Jorge E. [UNESP]; Dos Santos, Marcio Luiz; Riccardi, Carla Dos Santos [UNESP]; De Olyveira, Gabriel Molina [UNESP]; Hernandez-Escalona, Margarita; Basmaji, Pierre; Veranes-Pantoja, Yaymarilis; Guastaldi, Antonio Carlos [UNESP] (Editura Acad Romane, 2017)
Biomaterials are suitable for treating or relieving the symptoms of certain diseases or injuries, and they are also used for replacing damaged tissue or organs and modifying a patient's anatomy or physiological process. Currently, biomaterials are an important part of the medical industry. Bacterial cellulose is a biomaterial with great potential in several applications due to its characteristics and high purity. These characteristics allow its application in the confection of scaffolds for tissue regeneration, medical applications and nanocomposites. In this work, the bacterial cellulose was modified by acid treatment with sulfuric acid. The effect of sulfuric acid on bacterial cellulose was analyzed using thermogravimetric analysis, differential scanning calorimetry, X-ray powder diffraction, FTIR spectroscopy and scanning electron microscopy. The results showed that the solubility of the initial sample increased by approximately 18%, while the yield exceeded 80%. On the other hand, a decrease of the crystallinity index, which facilitated solubility, was observed. The increase of the sulfuric acid concentration favored this process and, as a result, a material with a different morphological surface was obtained.
Keywords: bacterial cellulose; crystallinity index; infrared spectroscopy; hydrogen bond intensity; lateral order index; X-ray diffraction